2011
DOI: 10.2474/trol.6.207
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Abrasive Wear Rate of VGCF/Polyamide 6 Composite Fibers

Abstract: The tribological properties under abrasive wear conditions, the tensile properties, the thermal properties and the structure have been investigated on the polyamide 6 (PA6) fibers dispersed with vapor-grown carbon fibers (VGCF's) in order to analyze the effects of dispersing VGCF's on the wear resistance of PA6 fibers. The wear resistance of the fibers have been determined using a method previously proposed by the present authors. The coefficient of friction decreased by dispersing a small amount of VGCF's but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In general, the interfacial junctions are influenced by the nature of the mated surfaces as well as by the surface chemistry and the stresses in the surface layers. Toshihira Irisawa et al [18,19] showed in their work that coefficient of friction can be represented by following equation,…”
Section: Hardness Evaluationmentioning
confidence: 98%